2022
DOI: 10.1186/s12906-022-03729-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanisms of kaempferol against endometriosis based on network pharmacology and in vitro experiments

Abstract: Endometriosis is a common gynecological disease, and its underlying mechanisms remain elusive. Patients are at a higher risk of recurrence after surgery or drug withdrawal. In this study, to identify a potentially effective and safe therapy for endometriosis, we screened potential target genes of kaempferol on endometriosis using network pharmacology and further validation. Network pharmacology showed kaempferol may suppress migratory and invasive properties by modulating the phosphoinositide 3-kinase (PI3K) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…The activation of β-catenin triggers the Epithelial-Mesenchymal Transition (EMT) in endometrial epithelial cells via TGF-β2, and inhibiting TGF-β effectively suppresses the EMT-related effects of β-catenin activation [140]. Moreover, it is suggested that kaempferol plays a role in regulating genes associated with PI3K, particularly Phosphatase and Tensin Homologue (PTEN), and MMP9, thereby inhibiting endometrial cell implantation and ectopic formation [141]. Proteins linked to adhesion and implantation have also been detected in endometriotic cells through appropriate staining.…”
Section: Cytoskeletal Proteins: Potential Contributors In Endometriosismentioning
confidence: 99%
“…The activation of β-catenin triggers the Epithelial-Mesenchymal Transition (EMT) in endometrial epithelial cells via TGF-β2, and inhibiting TGF-β effectively suppresses the EMT-related effects of β-catenin activation [140]. Moreover, it is suggested that kaempferol plays a role in regulating genes associated with PI3K, particularly Phosphatase and Tensin Homologue (PTEN), and MMP9, thereby inhibiting endometrial cell implantation and ectopic formation [141]. Proteins linked to adhesion and implantation have also been detected in endometriotic cells through appropriate staining.…”
Section: Cytoskeletal Proteins: Potential Contributors In Endometriosismentioning
confidence: 99%
“…The keyword "obesity" was searched in three different disease gene databases: (1) GeneCards Human Gene database (https://www.genecards.org/); (2) DisGeNET database (https://www.disgenet.org/home/); (3) Online Mendelian Inheritance in Man (OMIM) database (https://omim.org/). UniProt (http://www.UniProt.org) was used to obtain the gene symbols of all targets (obesity and kudingcha), and the information was used for subsequent network pharmacological data analysis (Zhao et al 2022).…”
Section: Prediction Of Endometriosis Targetsmentioning
confidence: 99%
“…After processing the data by R software (R version 4.1.2), we obtained the top 30 hub genes. Subsequently, we imported the hub gene data into the Cy software and obtained the HUB gene PPI network diagram (Zhao et al 2022).…”
Section: Protein-protein Interaction (Ppi) Network Constructionmentioning
confidence: 99%
“…(3) Online Mendelian Inheritance in Man (OMIM) database (https://omim.org/). UniProt (http://www.UniProt.org) was used to obtain the gene symbols of all targets (obesity and kudingcha), and the information was used for subsequent network pharmacological data analysis [12].…”
Section: Prediction Of Endometriosis Targetsmentioning
confidence: 99%
“…After processing the data by R software (R version 4.1.2), we obtained the top 30 hub genes. Subsequently, we imported the hub gene data into the Cy software and obtained the HUB gene PPI network diagram [12].…”
Section: Protein-protein Interaction (Ppi) Network Constructionmentioning
confidence: 99%